A method for preparing highly dispersed metal particle anchoring catalyst based on photothermal coupling subcritical technology and its application

The photothermal coupling subcritical technology achieves high dispersion and anchoring of metal particles in catalyst preparation, solving the problems of agglomeration, uneven dispersion and unstable anchoring in traditional catalyst preparation methods, and significantly improving the catalytic efficiency and service life.

CN119425739BActive Publication Date: 2025-03-21ZHEJIANG UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510033224.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-03-21
Estimated Expiration
2045-01-09

AI Technical Summary

Technical Problem

The traditional catalyst preparation method has the problems of agglomeration, uneven dispersion, and unsolid anchoring of the catalyst particles, resulting in reduced catalytic efficiency and poor reusability.

Method used

The photothermal coupling subcritical technology is adopted to achieve high dispersion and anchoring of metal particles by ultrasonic mixing of metal salts and carrier materials in ultrapure water, and heating and light irradiation in the photothermal coupling reactor.

Benefits of technology

It significantly improves the catalytic efficiency and reaction rate of the catalyst, extends the service life of the catalyst, reduces the replacement frequency and cost, and is suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119425739B_ABST
    Figure CN119425739B_ABST
Patent Text Reader

Abstract

The present application discloses a method and application for preparing a highly dispersed metal particle anchoring catalyst based on photothermal coupling subcritical technology; the preparation method of the catalyst of the present invention is: after the metal salt and the carrier material are uniformly dispersed in ultrapure water, they are transferred to a photothermal coupling reactor and sealed; under the conditions of heating, pressurization and visible light irradiation, a subcritical fluid is formed; the high temperature environment significantly improves the dispersion of the metal particles, and the combined effect of high pressure and light strengthens the interaction between the carrier and the nanoparticles, thereby improving the anchoring stability of the catalyst. Compared with the traditional photodeposition chemical method, the catalyst prepared by the method of the present invention has obvious advantages in dispersibility and stability, and exhibits excellent catalytic performance in the fields of biomass catalytic oxidation and sterilization reactions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of metal supported catalyst preparation, and in particular to a method for preparing a highly dispersed metal particle anchor catalyst based on a photothermal coupling subcritical technology and an application thereof. Background Art

[0002] In the field of catalytic technology, the dispersion and anchoring of catalysts are one of the key factors affecting catalytic performance. Traditional catalyst preparation methods have problems such as catalyst particle agglomeration, uneven dispersion, and weak anchoring, which lead to reduced catalytic efficiency and poor reusability. Therefore, it is of great significance to develop a new method for preparing highly dispersed metal particle anchored catalysts.

[0003] At present, there are many methods for preparing metal-supported catalysts, including physical mixing, chemical precipitation, sol-gel, impregnation, etc. However, these methods have limitations to varying degrees when preparing highly dispersed metal particle anchored catalysts. For example, although the physical mixing method and impregnation method are simple, it is difficult to ensure the uniform dispersion of catalyst particles; although the chemical precipitation method can prepare relatively uniform catalyst particles, it often has the problem of weak anchoring; although the sol-gel method can prepare highly dispersed catalysts, the preparation process often requires high-temperature calcination.

[0004] High-temperature and high-pressure fluids under subcritical conditions have excellent solubility and mass transfer properties. By utilizing these characteristics of subcritical fluids, high dispersion and effective anchoring of metal particles can be achieved during the catalyst preparation process. Photothermal coupling technology is a new technology that combines light energy with thermal energy. The photothermal effect can significantly increase the temperature and energy density of the reaction system, thereby accelerating the chemical reaction. Introducing photothermal coupling technology into the subcritical water system can further enhance the dispersion effect and anchoring strength during the catalyst preparation process. Photothermal coupling subcritical technology can not only utilize the non-contact heating characteristics of light energy to avoid the problems of thermal stress concentration and local overheating that may be caused by traditional heating methods, but also enhance the anchoring effect of metal particles on the catalyst carrier through the promotion of photochemical reactions. Summary of the invention

[0005] In order to overcome the shortcomings and deficiencies in the prior art, the purpose of the present invention is to provide a method and application for preparing a highly dispersed metal particle anchor catalyst based on photothermal coupling subcritical technology.

[0006] The technical solution adopted by the present invention is as follows:

[0007] A method for preparing a highly dispersed metal particle anchoring catalyst based on a photothermal coupling subcritical technology comprises the following steps:

[0008] Step 1: Disperse the metal salt and the carrier material in ultrapure water, mix them evenly by ultrasonication, and then transfer them into a photothermal coupling reactor, wherein the photothermal coupling reactor is provided with a quartz window, and a light source is provided outside the quartz window;

[0009] The metal salt is at least one of the nitrates and chlorides corresponding to copper, nickel and ruthenium;

[0010] The carrier material is at least one of monometallic sulfide MoS2, polymetallic oxide CoFe2O4, and polymetallic sulfide ZnLn2S4;

[0011] Step 2: introducing H2 or N2 into the mixed liquid in the photothermal coupling reactor to replace the air in the photothermal coupling reactor, then stopping the introduction of gas, sealing the reactor and stirring the mixed liquid, heating and raising the temperature in the reactor to 150-220°C and the pressure to 1.5-2.5MPa, turning on the light source to irradiate the mixed liquid, controlling the visible light band to 420-630nm, and maintaining the load under stirring for 30-90min;

[0012] Step 3: After the mixed solution obtained in step 2 is cooled, it is centrifuged and the obtained solid is washed with ultrapure water and anhydrous ethanol and then vacuum dried to obtain a highly dispersed metal particle anchor catalyst.

[0013] Furthermore, in step 1, the dispersion concentration of the carrier material in ultrapure water is 0.5-5 g / L, and the mass of the metal element in the metal salt is 0.5-4% of the mass of the carrier material.

[0014] Furthermore, the light source in step 2 is a 200W-400W xenon lamp with a wavelength range of 420-630nm.

[0015] Furthermore, in step 2, the temperature in the reactor is 160-200° C. and the pressure is 1.5-2.0 MPa, and the stirring load time in step 2 is 60-80 min.

[0016] The metal particles highly dispersed anchoring catalyst prepared by the method of the present invention are copper, nickel or ruthenium, and the mass of the metal is 0.5-4% of the mass of the carrier material.

[0017] The present invention also provides the use of the highly dispersed metal particle anchored catalyst in photocatalytic harmful bacteria disinfection, wherein the metal in the catalyst is copper, the carrier material is monometallic sulfide MoS2 or polymetallic sulfide Znln2S4, the mass of the metal element is 1-4% of the mass of the carrier material, and the photocatalytic application method is: putting the catalyst into a harmful bacteria solution, stirring at room temperature, and under the irradiation of a 100-300W xenon lamp light source, controlling the visible light band at 420-630nm through optical elements to carry out a multiphase catalytic water disinfection reaction.

[0018] The present invention also provides the application of the highly dispersed metal particle anchored catalyst in the photocatalytic degradation of organic pollutants in water. The metal in the catalyst is nickel, the carrier material is the polymetallic sulfide Znln2S4, the mass of the metal element is 3-4% of the mass of the carrier material, and the photocatalytic application method is: adding the catalyst to an aqueous solution of organic pollutants, stirring, adjusting the pH value to 1 ± 0.2, stirring at room temperature, first stirring for 20-60 minutes in a dark environment to reach adsorption-desorption equilibrium, and then conducting a photocatalytic degradation reaction under irradiation with a 200-400W Xe lamp light source and a cutoff filter of 420 nm.

[0019] The present invention also provides the use of the highly dispersed metal particle anchoring catalyst in a photocatalytic oxidation reaction, wherein the metal in the catalyst is ruthenium, the carrier material is a multi-metal oxide CoFe2O4, the mass of the metal element is 3-4% of the mass of the carrier material, and the catalyst is used to catalyze the reaction of oxidizing HMF to prepare FDCA, and the reaction process is: HMF, alkali, catalyst and oxidant are dispersed in water, ultrasonically mixed uniformly, the mixed solution is transferred to a high-pressure reactor and sealed, heated to 100-130°C and stirred for reaction for 8-12h; the mass of the catalyst is 70-80% of the mass of HMF, and the molar ratio of the alkali to HMF is 1.5-2:1. The oxidant is tert-butyl hydroperoxide, and the molar amount of the oxidant is 15-20 times the molar amount of HMF.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] 1) The present invention utilizes the synergistic effect of photothermal coupling and subcritical environment to effectively promote the high dispersion of metal particles on the catalyst carrier, greatly increasing the number of active sites, thereby significantly improving the catalytic efficiency and reaction rate of the catalyst, and is suitable for a variety of chemical reaction processes.

[0022] 2) Under subcritical conditions, the interaction between metal particles and the carrier is optimized to form a stable chemical bond, which effectively prevents the metal particles from falling off and agglomerating during the reaction, prolongs the service life of the catalyst, and reduces the replacement frequency and cost.

[0023] 3) The preparation technology of the catalyst of the present invention is simple to operate, the reaction conditions are easy to control, and it is suitable for large-scale industrial production, which is conducive to the batch preparation and cost control of catalyst products, and provides strong support for industrial application. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 It is a schematic diagram of the structure of the photothermal coupling reactor in the present invention; Figure 1 In the figure, 1-reactor, 2-gas cylinder, 3-light source, 4-quartz window, 5-magnetic stirrer.

[0025] Figure 2 EDS image of 1.0wt% Cu / MoS2 catalyst prepared in Example 1;

[0026] Figure 3 EDS image of 1.0wt% Cu / ZnIn2S4 catalyst prepared in Example 2;

[0027] Figure 4 EDS image of 4.0wt% Ni / ZnIn2S4 catalyst prepared in Example 3;

[0028] Figure 5 Example 3 prepared by the catalyst catalytic degradation of sulfamethoxazole effect diagram;

[0029] Figure 6 Recyclability diagram of the catalyst prepared in Example 3;

[0030] Figure 7 EDS image of 4.0wt% Ru / FeCo2O4 catalyst prepared in Example 4;

[0031] Figure 8 Example 4 prepared catalytic oxidation effect diagram of the catalyst;

[0032] Fig. 9 Recyclability diagram of the catalyst prepared in Example 4;

[0033] Fig.10 EDS image of 1.0wt% Cu / ZnIn2S4 catalyst prepared in Comparative Example 1;

[0034] Fig.11 EDS image of 1.0wt% Cu / ZnIn2S4 catalyst prepared in Comparative Example 2;

[0035] Fig.12 EDS image of 1.0wt% Cu / ZnIn2S4 catalyst prepared in Comparative Example 3;

[0036] Fig.13 EDS image of 1.0wt% Cu / ZnIn2S4 catalyst prepared in Comparative Example 4;

[0037] Fig.14 EDS image of 1.0wt% Cu / ZnIn2S4 catalyst prepared in Comparative Example 5;

[0038] Fig.15 EDS image of 1.0wt% Cu / ZnIn2S4 catalyst prepared in Comparative Example 6. DETAILED DESCRIPTION

[0039] The present invention will be further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.

[0040] The structural diagram of the photothermal coupling reactor used in the embodiment of the present invention is shown in FIG. Figure 1 As shown, the photothermal coupling reactor includes a reactor 1 with a heating device, the material of the reactor 1 is stainless steel, a quartz window 4 is provided on the top of the reactor 1, and a light source 3 is provided outside the quartz window 4. A stirring magnet is added inside the reactor 1, and the reactor 1 is placed on a magnetic stirrer 5. A gas inlet and a gas outlet are provided on the top of the reactor 1. The gas inlet is connected to the gas cylinder 2 through an inlet pipe with an inlet valve, and the gas outlet is connected to the exhaust pipe, and an outlet valve is provided on the exhaust pipe.

[0041] Example 1 Preparation of 1.0wt% Cu / MoS2 catalyst using photothermal coupling subcritical technology, the steps are as follows:

[0042] 1) Dissolve 2.47g (NH4)2MoO4 and 2.284g NH2CSNH2 in 70mL water in turn and stir for 30min to ensure complete mixing to form a mixed solution A; then adjust the pH of solution A to 7.0 with 1 M NaOH solution to obtain solution B, and transfer it to a hydrothermal reactor with a 100mL polytetrafluoroethylene liner; the hydrothermal reactor is sealed and transferred to an oven, heated to 200℃ and maintained for 24h, and then taken out after cooling to room temperature to obtain a mixed solution C containing a precipitate; centrifuge solution C at 8000rpm for 5min to obtain a black solid precipitate; wash it three times with ultrapure water and anhydrous ethanol each to obtain a black solid material, and finally dry it in a vacuum oven at 60℃ for 8h to obtain a MoS2 material with a three-dimensional nanoflower ball structure.

[0043] 2) Disperse 2.1 mg CuCl2 and 100 mg MoS2 in 50 mL ultrapure water and disperse them evenly by ultrasonication; put the mixed solution into a stainless steel photothermal coupling reactor and seal the photothermal coupling reactor. Figure 1 The gas inlet on the photothermal coupling reactor is connected to the hydrogen cylinder through an inlet pipe with an inlet valve, the inlet valve and the outlet valve are opened, and the air and dissolved oxygen in the system are removed by hydrogen, and then the normal pressure is maintained, and the inlet valve is closed to maintain magnetic stirring. The reaction liquid in the photothermal coupling reactor is heated to 200°C, the pressure is 1.5MPa, the xenon lamp light source is turned on, the xenon lamp power is 300W, and the visible light band is controlled at 420-630nm. The reaction lasts for 60min and then centrifuged. The obtained solid is washed with water and anhydrous ethanol for 3 times, respectively, and vacuum dried at 60°C to obtain the 1.0wt% Cu / MoS2 catalyst with a three-dimensional structure.

[0044] The EDX image of the 1.0wt% Cu / MoS2 catalyst prepared in Example 1 is as follows: Figure 2 As shown, from Figure 2 It can be seen that in the 1.0wt% Cu / MoS2 catalyst of Example 1, Cu atoms are highly dispersed on the surface of the MoS2 material.

[0045] The 1.0wt% Cu / MoS2 catalyst prepared in Example 1 is used to disinfect harmful bacteria, and the operation steps are as follows:

[0046] S1: First, prepare a 10 8 CFU / mL of Pseudomonas aeruginosa suspension, then take 20mL PBS buffer solution and add 0.02g of the 1.0wt% Cu / MoS2 catalyst, ultrasonically treat for 2min to ensure that the catalyst is evenly dispersed in the solution, then add 0.2mL of the prepared Pseudomonas aeruginosa suspension under magnetic stirring and room temperature of 25℃, turn on a 150W xenon lamp to simulate sunlight, control the visible light band at 420-630nm through optical elements, and carry out multiphase catalytic water disinfection reaction. Sampling is performed every 15min, and the total disinfection reaction is 80min.

[0047] The disinfecting effect of 1.0wt% Cu / MoS2 on Pseudomonas aeruginosa in this case is shown in Table 1. As can be seen from Table 1, Pseudomonas aeruginosa in the water body was completely inactivated after 80 minutes.

[0048] S2: The 1.0wt% Cu / MoS2 in the residual liquid after 80 minutes of the disinfection reaction in step S1 is separated by centrifugation, and then washed alternately with ultrapure water and anhydrous ethanol for multiple times, and the catalyst is recovered and regenerated after vacuum drying at 60°C. The recovered catalyst is subjected to the next batch of sterilization experiments according to the method and steps of step S1 to realize the recycling of the disinfectant. By analogy, the sterilization test data of the catalyst is tested for 5 cycles, and the experimental results are shown in Table 1.

[0049] Table 1 Sterilization effect and recycling effect of 1.0wt% Cu / MoS2

[0050] .

[0051] As can be seen from Table 1, the 1.0wt% Cu / MoS2 in Example 1 is used for efficient disinfecting of harmful bacteria and has good reusability against Pseudomonas aeruginosa. After 1.0wt% Cu / MoS2 is recycled for 5 times, the sterilization effect does not change significantly.

[0052] Example 2 Preparation of 1.0wt% Cu / ZnIn2S4 catalyst using photothermal coupling subcritical technology, the steps are as follows:

[0053] 1) 0.068g ZnCl2, 0.239g InCl2·4H2O and 0.15g CH3CSNH2 were dissolved in 40mL water in turn and mixed evenly to prepare 40mL of mixed metal salt solution A, and then the pH was adjusted to 1.0 with 5M HCl solution to obtain solution B, and B was transferred to a hydrothermal reactor with a polytetrafluoroethylene liner. The hydrothermal reactor was sealed and transferred to an oven, heated to 160℃ and maintained for 16h, and then taken out after cooling to room temperature. At this time, the mixed solution C contained precipitate; then, it was washed three times with ultrapure water and anhydrous ethanol respectively to obtain a yellow solid, and finally dried in a vacuum oven at 60℃ for 12h, thereby successfully preparing a three-dimensional flower-like structure material ZnIn2S4.

[0054] 2) Disperse 2.1 mg CuCl2 and 100 mg ZnIn2S4 in 50 mL ultrapure water and disperse them evenly by ultrasonication; place the mixed solution into a photothermal coupling reactor made of stainless steel and seal the photothermal coupling reactor. Figure 1 The gas inlet on the photothermal coupling reactor is connected to the hydrogen cylinder through an inlet pipe with an inlet valve, the inlet valve and the outlet valve are opened, and hydrogen is passed to remove air and dissolved oxygen in the system. After that, the outlet valve is closed, and pressurized H2 is passed until the pressure in the photothermal coupling reactor reaches 1MPa, and then the inlet valve is closed, and magnetic stirring is maintained; after heating to 160°C, the pressure is 2MPa, and the xenon lamp light source is turned on, the xenon lamp power is 300W, and the visible light band is controlled at 420-630nm. The reaction lasts for 60min and then centrifuged, and the obtained solid is washed with water and anhydrous ethanol for 3 times, respectively, and dried in vacuo at 60°C to obtain the 1.0wt% Cu / ZnIn2S4 catalyst with a three-dimensional structure.

[0055] The EDX image of the 1.0wt% Cu / ZnIn2S4 catalyst prepared in Example 2 is as follows: Figure 3 As shown, from Figure 3 It can be seen that in the 1.0wt% Cu / ZnIn2S4 catalyst of Example 2, Cu atoms are highly dispersed on the surface of the ZnIn2S4 material.

[0056] The 1.0wt% Cu / ZnIn2S4 catalyst prepared in Example 2 is used to disinfect harmful bacteria, and the operation steps are as follows:

[0057] S1: First, prepare a 10 8CFU / mL of Pseudomonas aeruginosa suspension, then take 20mL PBS buffer solution and add 0.02g catalyst, ultrasonicate for 2min to ensure that the catalyst is evenly dispersed in the solution, then add 0.2mL of Pseudomonas aeruginosa suspension under magnetic stirring and room temperature of 25℃, turn on a 150W xenon lamp to simulate sunlight, control the visible light band at 420-630nm through optical elements, and carry out multiphase catalytic water disinfection reaction. Sampling is done every 20min, and the total disinfection reaction time is 80min.

[0058] In this case, 1.0wt% Cu / ZnIn2S4 was used to efficiently disinfect harmful bacteria, and the disinfecting effect on Pseudomonas aeruginosa is shown in Table 2. As can be seen from Table 2, Pseudomonas aeruginosa in the water was completely inactivated after 80 minutes.

[0059] S2: The 1.0wt% Cu / ZnIn2S4 in the residual liquid after 80 minutes of the disinfection reaction in step S1 is separated by centrifugation, and then washed alternately with ultrapure water and anhydrous ethanol for multiple times, and the catalyst is recovered and regenerated after vacuum drying at 60°C. The recovered catalyst is subjected to the next batch of sterilization experiments according to the method and steps of step S1 to realize the recycling of the disinfectant. By analogy, the sterilization experimental data of the catalyst was tested for 5 cycles, and the experimental results are shown in Table 2.

[0060] The 1.0wt% Cu / ZnIn2S4 in Example 2 is used to disinfect harmful bacteria. The reusability effect of 1.0wt% Cu / ZnIn2S4 is shown in Table 2. After 1.0wt% Cu / ZnIn2S4 is recycled for 5 times, the sterilization effect does not change significantly.

[0061] Example 3 Preparation of 4.0wt% Ni / ZnIn2S4 by photothermal coupling subcritical technology, the steps are as follows:

[0062] 1) The preparation method of ZnIn2S4 is consistent with that in Example 2.

[0063] 2) Disperse 19.6 mg Ni(NO3)2·6H2O and 100 mg ZnIn2S4 in 50 mL ultrapure water and disperse them evenly by ultrasonication; place the mixture into a photothermal coupling reactor made of stainless steel and seal the photothermal coupling reactor. Figure 1The gas inlet on the photothermal coupling reactor is connected to the hydrogen cylinder through an inlet pipe with an inlet valve, the inlet valve and the outlet valve are opened, and hydrogen is passed to remove air and dissolved oxygen in the system. After that, the outlet valve is closed, and pressurized H2 is passed until the pressure in the photothermal coupling reactor reaches 1MPa, and then the inlet valve is closed to maintain magnetic stirring; after heating to 160°C, the pressure is 2MPa, and the xenon lamp light source is turned on, the xenon lamp power is 300W, and the visible light band is controlled at 420-630nm. The reaction lasts for 60min and then centrifuged. The obtained solid is washed with water and anhydrous ethanol for 3 times, respectively, and dried in vacuo at 60°C to obtain the 4.0wt% Ni / ZnIn2S4 catalyst with a three-dimensional structure.

[0064] The EDX image of the 4.0wt% Ni / ZnIn2S4 catalyst prepared in Example 3 is as follows: Figure 4 As shown, from Figure 4 It can be seen that in the 4.0wt% Ni / ZnIn2S4 catalyst of Example 3, Ni atoms are highly dispersed on the surface of the ZnIn2S4 material.

[0065] The 4.0% Ni / ZnIn2S4 or ZnIn2S4 catalyst prepared in Example 3 is used for the degradation of sulfamethoxazole SMX, and the operation steps are as follows:

[0066] S1: 10 mg of catalyst was added to 50 mL of aqueous solution containing SMX (1.5 mg / L). The reaction mixture was ultrasonicated for 1 min, and the initial pH value was adjusted within the deviation range of 1 ± 0.2. The reaction mixture was transferred to a quartz reactor, and a stirring magnet was added thereto. The quartz reactor was placed on a magnetic stirrer and stirred in the dark for 30 min. After SMX and the photocatalyst reached adsorption-desorption equilibrium, the reaction was immediately irradiated with light. The light source was a 300W Xe lamp and the cutoff filter was 420 nm. Samples were taken every 15 min under the light reaction, and the total light reaction was 60 min.

[0067] According to the above experimental process, the 4.0% Ni / ZnIn2S4 or ZnIn2S4 catalyst prepared in Example 3 was used for the degradation of sulfamethoxazole. The degradation effect of sulfamethoxazole was as follows: Figure 5 As shown in . Figure 5 It can be seen that the catalytic activity of 4.0% Ni / ZnIn2S4 is significantly higher than that of ZnIn2S4. After 60 minutes of catalytic degradation by 4.0% Ni / ZnIn2S4, 93.1% of sulfamethoxazole in water has been degraded.

[0068] S2: The 4.0wt% Ni / ZnIn2S4 in the residual liquid after the 4.0% Ni / ZnIn2S4 catalyzed light reaction for 60 minutes in step S1 was separated by centrifugation, and then washed alternately with ultrapure water and anhydrous ethanol for multiple times, and then vacuum dried at 60°C and subjected to degradation experiments again to achieve the recycling of the catalyst. The recyclability of 4.0wt% Ni / ZnIn2S4 is shown in Figure 2. Figure 6 As shown in the figure, after 4.0wt% Ni / ZnIn2S4 was recycled for 5 times, the catalytic degradation effect did not change significantly. Figure 6 In the cycle where each catalyst is reused, the cycle time of 80 min is divided into two stages, namely a 30-min dark treatment stage and a 60-min light reaction stage.

[0069] Example 4 Preparation of 4.0wt%Ru / FeCo2O4 using photothermal coupling subcritical technology, the steps are as follows:

[0070] 1) Dissolve 1mmol Fe(NO3)3·9H2O, 2mmol Fe(NO3)3·9H2O and 3mmol monohydrated citric acid in 60mL deionized water and mix thoroughly. Next, pour the mixed solution into a preheated flask and heat it in a water bath at 65°C. Then, slowly add sodium hydroxide to the solution, and keep the molar ratio of sodium hydroxide to Fe metal salt at 1:6, that is, the amount of sodium hydroxide added is 0.5mmol, and stir in a water bath for 60min. Adjust the pH value of the solution to 13 by adding ammonia water, stir again, transfer the solution to a 200°C polytetrafluoroethylene hydrothermal reactor and seal it for 5h of hydrothermal treatment. After the hydrothermal treatment is completed, let the reactor cool down naturally to room temperature. Wash the resulting precipitate with deionized water and anhydrous ethanol respectively until the washing liquid is neutral, and then dry it to finally obtain the iron cobalt spinel nanocatalyst FeCo2O4.

[0071] 2) Dissolve 8.2 mg RuCl3 and 100 mg FeCo2O4 in 50 mL ultrapure water and disperse them evenly by ultrasonication; put the mixed solution into a photothermal coupling reactor made of stainless steel and seal the photothermal coupling reactor. Figure 1The gas inlet on the photothermal coupling reactor is connected to the nitrogen cylinder through an inlet pipe with an inlet valve, the inlet valve and the outlet valve are opened, and nitrogen is passed to remove air and dissolved oxygen in the system. After that, the outlet valve is closed to maintain normal pressure, and then the inlet valve is closed to maintain magnetic stirring; after heating to 200°C, the pressure reaches 1.5MPa, and the xenon lamp light source is turned on, the xenon lamp power is 300W, and the visible light band is controlled at 420-630nm. The reaction lasts for 60min and then centrifuged. The obtained solid is washed with water and anhydrous ethanol for 3 times, respectively, and dried in vacuo at 60°C to obtain the 4.0wt% Ru / FeCo2O4 catalyst with a three-dimensional structure.

[0072] The EDX of the 4.0wt% Ru / FeCo2O4 catalyst prepared in Example 4 is as follows Figure 7 As shown, from Figure 7 It can be seen that in the 4.0 wt% Ru / FeCo2O4 catalyst prepared in Example 4, Ru atoms are highly dispersed on the surface of the FeCo2O4 material.

[0073] The 4.0wt% Ru / FeCo2O4 ruthenium-based spinel catalyst material prepared in Example 4 was used for biomass oxidation, and the operation steps were as follows:

[0074] S1: 0.5 mmol 5-hydroxymethylfurfural (HMF), 1 mmol NaOH and 50 mg 4.0wt% / FeCo2O4 catalyst were added to the reactor, 9 mmol tert-butyl hydroperoxide (t-BuOOH) was added as an oxidant, and ultrapure water was used as a solvent to control the liquid volume to 20 mL. After ultrasonic mixing, the mixed solution was transferred to a micro-autoclave and sealed, and the magnetic stirring was turned on after the temperature was raised to 120 °C, and the speed was controlled at 500 rpm. Samples were taken for analysis at regular intervals, filtered with a 0.22 μm filter membrane, and quantitatively analyzed by high performance liquid chromatography (HPLC).

[0075] According to the above experimental process, the 4.0wt% Ru / FeCo2O4 catalyst of Example 4 was used for biomass oxidation, and the oxidation effect on HMF was as follows: Figure 8 As shown. Figure 8 It can be seen that after 8 h, 99% of the HMF in the water has been converted.

[0076] S2: The 4.0% Ru / FeCo2O4 in the residual liquid after the reaction for 20 hours under the catalysis of 4.0% Ru / FeCo2O4 in step S1 is separated by centrifugation, and then washed alternately with ultrapure water and anhydrous ethanol for multiple times, and then vacuum dried at 60°C and subjected to catalytic oxidation experiments again to achieve the recycling of the catalyst. The recovered catalyst is subjected to the next batch of catalytic experiments according to the method and steps of step S1 to achieve the recycling of the catalyst. By analogy, the catalytic experimental data of the catalyst being recycled 5 times are tested, and the experimental results are shown in Fig. 9 The recyclability of 4.0wt% Ru / FeCo2O4 is shown in Fig. 9 As shown, the oxidation effect of 4.0wt% Ru / FeCo2O4 did not change significantly after being recycled for 5 times.

[0077] Comparative Example 1: 1.0wt% Cu / ZnIn2S4 catalyst was prepared by photothermal coupling subcritical technology (normal temperature and pressure), and the steps were as follows:

[0078] 1) The preparation method of ZnIn2S4 is consistent with that in Example 2.

[0079] 2) Disperse 2.1 mg CuCl2 and 100 mg ZnIn2S4 in 50 mL ultrapure water and disperse them evenly by ultrasonication; put the mixed solution into a quartz photoreactor, introduce hydrogen to remove dissolved oxygen in the system, maintain normal pressure, control the normal temperature with a constant temperature water bath, and maintain magnetic stirring; turn on the xenon lamp with a power of 300 W, control the visible light band at 420-630 nm, continue the photodeposition reaction for 1 hour, and then centrifuge and separate. Wash the obtained solid with water and anhydrous ethanol for 3 times, respectively, and dry it in a vacuum at 60°C to obtain the 1.0 wt% Cu / ZnIn2S4 composite functional material with a three-dimensional structure.

[0080] The EDS image of the 1.0wt% Cu / ZnIn2S4 catalyst prepared in Comparative Example 1 is as follows: Fig.10 As shown, from Fig.10 It can be seen that in the 1.0 wt% Cu / ZnIn2S4 catalyst prepared in Comparative Example 1, the Cu atoms are unevenly distributed.

[0081] The 1.0wt% Cu / ZnIn2S4 catalyst prepared in Comparative Example 1 was used to disinfect harmful bacteria such as Pseudomonas aeruginosa, and the operation steps were as follows:

[0082] S1: First, prepare a 10 8CFU / mL of Pseudomonas aeruginosa suspension, then take 20mL PBS buffer solution and add 0.02g catalyst, ultrasonicate for 2min to ensure that the catalyst is evenly dispersed in the solution, then add 0.2mL of Pseudomonas aeruginosa suspension under magnetic stirring and room temperature of 25℃, turn on a 150W xenon lamp to simulate sunlight, control the visible light band at 420-630nm through optical elements, and carry out multiphase catalytic water disinfection reaction. Sampling is done every 20min, and the total disinfection reaction time is 80min.

[0083] The 1.0wt% Cu / ZnIn2S4 in Comparative Example 1 is used for efficient disinfecting of harmful bacteria, and the disinfecting effect on Pseudomonas aeruginosa is shown in Table 2. As can be seen from Table 2, Pseudomonas aeruginosa in the water body was completely inactivated after 80 minutes.

[0084] S2: The 1.0wt% Cu / ZnIn2S4 in the residual liquid after 80 minutes of the sterilization reaction in step S1 is separated by centrifugation, and then washed alternately with ultrapure water and anhydrous ethanol for multiple times, and the catalyst is recovered and regenerated after vacuum drying at 60°C. The recovered catalyst is subjected to the next batch of sterilization experiments according to the method steps of step S1 to achieve the recycling of the disinfectant. By analogy, the sterilization experimental data of the catalyst was recycled 5 times, and the experimental results are shown in Table 2. As shown in Table 2, after the 1.0wt% Cu / ZnIn2S4 of Comparative Example 1 was recycled 5 times, the sterilization effect decreased significantly, indicating that the anchoring effect of Cu nanoparticles on the surface of ZnIn2S4 was poor.

[0085] Table 2 Effects of normal temperature and pressure on sterilization and recycling of catalyst materials

[0086] .

[0087] Comparative Example 2 Preparation of 1.0wt% Cu / ZnIn2S4 by photothermal coupling subcritical technology (heating without pressure)

[0088] 1) The preparation process of ZnIn2S4 is as described in Example 2.

[0089] 2) Disperse 2.1 mg CuCl2 and 100 mg ZnIn2S4 in 50 mL ultrapure water and disperse them evenly by ultrasonication; place the mixture into a photothermal coupling reactor made of stainless steel and seal the photothermal coupling reactor. Figure 1The gas inlet on the photothermal coupling reactor is connected to the hydrogen cylinder through an inlet pipe with an inlet valve, the inlet valve and the outlet valve are opened, and hydrogen is passed to remove air and dissolved oxygen in the system. After that, the outlet valve and the inlet valve are closed, that is, no additional pressurized H2 is introduced into the photothermal coupling reactor to make the internal H2 reach a pressurized state. The H2 pressure in the photothermal coupling reactor is 0.1 MPa at normal pressure, and magnetic stirring is maintained; after heating to 160°C, the pressure is 0.5 MPa, and the xenon lamp light source is turned on, the xenon lamp power is 300W, and the visible light band is controlled at 420-630nm. The reaction lasts for 60 minutes and then centrifuged. The obtained solid is washed with water and anhydrous ethanol for 3 times, respectively, and dried in vacuo at 60°C to obtain the 1.0wt% Cu / ZnIn2S4 catalyst with a three-dimensional structure.

[0090] The EDX image of the 1.0wt% Cu / ZnIn2S4 catalyst prepared in Comparative Example 2 is as follows: Fig.11 As shown, from Fig.11 It can be seen that in the 1.0 wt% Cu / ZnIn2S4 catalyst of Comparative Example 2, Cu atoms are highly dispersed on the surface of the ZnIn2S4 material.

[0091] The 1.0wt% Cu / ZnIn2S4 catalyst prepared in Comparative Example 2 was used to disinfect harmful bacteria, and the operation steps were as follows:

[0092] S1: First, prepare a 10 8 CFU / mL of Pseudomonas aeruginosa suspension, then take 20mL PBS buffer solution and add 0.02g catalyst, ultrasonicate for 2min to ensure that the catalyst is evenly dispersed in the solution, then add 0.2mL of Pseudomonas aeruginosa suspension under magnetic stirring and room temperature of 25℃, turn on a 150W xenon lamp to simulate sunlight, control the visible light band at 420-630nm through optical elements, and carry out multiphase catalytic water disinfection reaction. Sampling is done every 20min, and the total disinfection reaction time is 80min.

[0093] In this case, 1.0wt% Cu / ZnIn2S4 was used to efficiently disinfect harmful bacteria, and the disinfecting effect on Pseudomonas aeruginosa was shown in Table 3. As can be seen from Table 3, Pseudomonas aeruginosa in the water was completely inactivated after 80 minutes.

[0094] S2: The 1.0wt% Cu / ZnIn2S4 in the residual liquid after 80 minutes of the disinfection reaction in step S1 is separated by centrifugation, and then washed alternately with ultrapure water and anhydrous ethanol for multiple times, and the catalyst is recovered and regenerated after vacuum drying at 60°C. The recovered catalyst is subjected to the next batch of sterilization experiments according to the method steps of step S1 to achieve the recycling of the disinfectant. By analogy, the sterilization experimental data of the catalyst was recycled 5 times, and the experimental results are shown in Table 3. After the 1.0wt% Cu / ZnIn2S4 in Comparative Example 2 was recycled 5 times, the sterilization effect decreased, indicating that the low-pressure state is not conducive to the anchoring of Cu nanoparticles on the surface of ZnIn2S4.

[0095] Table 3 Effect of initial pressure on sterilization and recycling of catalyst materials

[0096] .

[0097] Comparative Example 3: Preparation of 1.0wt% Cu / ZnIn2S4 by light-thermal coupling subcritical technology (normal temperature pressurization), the steps are as follows:

[0098] 1) The preparation process of ZnIn2S4 is as described in Example 2.

[0099] 2) Disperse 2.1 mg CuCl2 and 100 mg ZnIn2S4 in 50 mL ultrapure water and disperse them evenly by ultrasonication; place the mixture into a photothermal coupling reactor made of stainless steel and seal the photothermal coupling reactor. Figure 1 The gas inlet on the photothermal coupling reactor is connected to the hydrogen cylinder through an inlet pipe with an inlet valve, the inlet valve and the outlet valve are opened, and hydrogen is passed to remove air and dissolved oxygen in the system. After that, the outlet valve and the inlet valve are closed, that is, no additional pressurized H2 is introduced into the photothermal coupling reactor to make the internal H2 reach a pressurized state, and the H2 pressure in the photothermal coupling reactor is 2MPa at normal pressure; maintain 25°C, turn on the xenon lamp light source, the xenon lamp power is 300W, and the visible light band is controlled at 420-630nm. The reaction lasts for 60min and then centrifuged. The obtained solid is washed with water and anhydrous ethanol for 3 times, respectively, and dried in vacuo at 60°C to obtain the 1.0wt% Cu / ZnIn2S4 catalyst with a three-dimensional structure.

[0100] The EDX image of the 1.0wt% Cu / ZnIn2S4 catalyst prepared in Comparative Example 3 is as follows: Fig.12 As shown, from Fig.12 It can be seen that in the 1.0 wt% Cu / ZnIn2S4 catalyst of Comparative Example 3, the dispersion of Cu atoms on the surface of the ZnIn2S4 material is worse than that of Example 2.

[0101] The 1.0wt% Cu / ZnIn2S4 catalyst prepared in Comparative Example 3 was used to disinfect harmful bacteria, and the operation steps were as follows:

[0102] S1: First, prepare a 10 8 CFU / mL of Pseudomonas aeruginosa suspension, then take 20mL PBS buffer solution and add 0.02g catalyst, ultrasonicate for 2min to ensure that the catalyst is evenly dispersed in the solution, then under magnetic stirring and room temperature of 25℃, add 0.2mL of Pseudomonas aeruginosa suspension, turn on a 150W xenon lamp to simulate sunlight (the visible light band is controlled at 420-630nm through optical elements), and carry out multiphase catalytic water disinfection reaction. Samples are collected every 20min, and the total disinfection reaction time is 80min.

[0103] In this case, 1.0wt% Cu / ZnIn2S4 is used to efficiently disinfect harmful bacteria, and the disinfecting effect on Pseudomonas aeruginosa is shown in Table 4. As can be seen from Table 4, after 80 minutes, 92% of Pseudomonas aeruginosa in the water was inactivated, which is a downward trend compared with the effect of Example 2.

[0104] S2: The 1.0wt% Cu / ZnIn2S4 in the residual liquid after 80 minutes of the disinfection reaction in step S1 is separated by centrifugation, and then washed alternately with ultrapure water and anhydrous ethanol for multiple times. After vacuum drying at 60°C, the sterilization experiment is carried out again to realize the recovery and regeneration of the catalyst of the disinfectant. The recovered catalyst is subjected to the next batch of sterilization experiments according to the method steps of step S1 to realize the recycling of the disinfectant. By analogy, the sterilization experimental data of the catalyst recycled 5 times are tested, and the experimental results are shown in Table 4. As shown in Table 4, the sterilization effect of 1.0wt% Cu / ZnIn2S4 does not change much after being recycled 5 times. However, the catalyst prepared at room temperature in Comparative Example 3 is not conducive to the dispersion of metal Cu on the carrier material, so its catalytic sterilization activity is not as good as that of Example 2.

[0105] Table 4 Effect of preparation temperature on sterilization and recycling of catalyst materials

[0106] .

[0107] Comparative Example 4: 1.0wt% Cu / ZnIn2S4 catalyst was prepared by photothermal coupling subcritical technology (ultraviolet region), and the steps were as follows:

[0108] 1) The preparation process of ZnIn2S4 is as described in Example 2.

[0109] 2) Disperse 2.1 mg CuCl2 and 100 mg ZnIn2S4 in 50 mL ultrapure water and disperse them evenly by ultrasonication; place the mixture into a photothermal coupling reactor made of stainless steel and seal the photothermal coupling reactor. Figure 1 The gas inlet on the photothermal coupling reactor is connected to the hydrogen cylinder through an inlet pipe with an inlet valve, the inlet valve and the outlet valve are opened, and hydrogen is passed to remove air and dissolved oxygen in the system. After that, the outlet valve and the inlet valve are closed, that is, no additional pressurized H2 is introduced into the photothermal coupling reactor to make the internal H2 reach a pressurized state, and the H2 pressure in the photothermal coupling reactor is 1 MPa at normal pressure; the temperature is raised to 160°C, the pressure is 2MPa, the xenon lamp light source is turned on, the xenon lamp power is 300W, the control band is 315-400nm, the reaction lasts for 60min and then centrifuged, the obtained solid is washed with water and anhydrous ethanol 3 times respectively, and dried in vacuo at 60°C to obtain the 1.0wt% Cu / ZnIn2S4 catalyst with a three-dimensional structure.

[0110] The EDX image of the 1.0wt% Cu / ZnIn2S4 catalyst prepared in Comparative Example 4 is as follows: Fig.13 As shown, from Fig.13 It can be seen that in the 1.0wt% Cu / ZnIn2S4 catalyst of Comparative Example 4, the dispersion of Cu atoms on the surface of the ZnIn2S4 material is also highly dispersed compared with that of Example 2.

[0111] The 1.0wt% Cu / ZnIn2S4 catalyst prepared in Comparative Example 4 was used to disinfect harmful bacteria, and the operation steps were as follows:

[0112] S1: First, prepare a 10 8 CFU / mL of Pseudomonas aeruginosa suspension, then take 20mL PBS buffer solution and add 0.02g catalyst, ultrasonicate for 2min to ensure that the catalyst is evenly dispersed in the solution, then under magnetic stirring and room temperature of 25℃, add 0.2mL of Pseudomonas aeruginosa suspension, turn on a 150W xenon lamp to simulate sunlight (the visible light band is controlled at 420-630nm through optical elements), and carry out multiphase catalytic water disinfection reaction. Samples are collected every 20min, and the total disinfection reaction time is 80min.

[0113] In this case, 1.0wt% Cu / ZnIn2S4 is used to efficiently disinfect harmful bacteria, and the disinfecting effect on Pseudomonas aeruginosa is shown in Table 5. As can be seen from Table 5, after 80 minutes, Pseudomonas aeruginosa in the water was inactivated by 100%, which is consistent with the effect of Example 2.

[0114] S2: The 1.0wt% Cu / ZnIn2S4 in the residual liquid after 80min of the disinfection reaction in step S1 is separated by centrifugation, and then washed alternately with ultrapure water and anhydrous ethanol for multiple times, and then the sterilization experiment is carried out again after vacuum drying at 60°C to realize the recovery and regeneration of the disinfectant catalyst. The recovered catalyst is subjected to the next batch of sterilization experiments according to the method steps of step S1 to realize the recycling of the disinfectant. By analogy, the sterilization experimental data of the catalyst recycling 5 times are tested, and the experimental results are shown in Table 5. As shown in Table 5, after the 1.0wt% Cu / ZnIn2S4 of comparative example 4 is recycled 5 times, the sterilization effect remains at 100%. This is because Cu ions have stronger absorption in the ultraviolet region, which is conducive to enhancing the interaction between Cu ions and carriers and enhancing the degree of anchoring. However, due to the energy consumption of ultraviolet light and the damage to the human body, visible light in the 420-630nm band is more advantageous when the application effect is similar.

[0115] Table 5 Effect of wavelength range on sterilization and recycling effects of catalyst materials

[0116] .

[0117] Comparative Example 5 Photothermal coupling subcritical technology (infrared light region) was used to prepare 1.0wt% Cu / ZnIn2S4 catalyst, and the steps were as follows:

[0118] 1) The preparation process of ZnIn2S4 is as described in Example 2.

[0119] 2) Disperse 2.1 mg CuCl2 and 100 mg ZnIn2S4 in 50 mL ultrapure water and disperse them evenly by ultrasonication; place the mixture into a photothermal coupling reactor made of stainless steel and seal the photothermal coupling reactor. Figure 1 The gas inlet on the photothermal coupling reactor is connected to the hydrogen cylinder through an inlet pipe with an inlet valve, the inlet valve and the outlet valve are opened, and hydrogen is passed to remove air and dissolved oxygen in the system. After that, the outlet valve and the inlet valve are closed, that is, no additional pressurized H2 is introduced into the photothermal coupling reactor to make the internal H2 reach a pressurized state, and the H2 pressure in the photothermal coupling reactor is 1 MPa at normal pressure; the temperature is raised to 160°C, the pressure is 2MPa, the xenon lamp light source is turned on, the xenon lamp power is 300W, the control band is 780-920nm, the reaction is continued for 60min and then centrifuged, the obtained solid is washed with water and anhydrous ethanol 3 times respectively, and dried in vacuo at 60°C to obtain the 1.0wt% Cu / ZnIn2S4 catalyst with a three-dimensional structure.

[0120] The EDX image of the 1.0wt% Cu / ZnIn2S4 catalyst prepared in Comparative Example 5 is as follows: Fig.14 As shown, from Fig.14It can be seen that in the 1.0wt% Cu / ZnIn2S4 catalyst of Comparative Example 5, the dispersion of Cu atoms on the surface of the ZnIn2S4 material is also highly dispersed compared with Example 2.

[0121] The 1.0wt% Cu / ZnIn2S4 catalyst prepared in Comparative Example 5 was used to disinfect harmful bacteria, and the operation steps were as follows:

[0122] S1: First, prepare a 10 8 CFU / mL of Pseudomonas aeruginosa suspension, then take 20mL PBS buffer solution and add 0.02g catalyst, ultrasonicate for 2min to ensure that the catalyst is evenly dispersed in the solution, then under magnetic stirring and room temperature of 25℃, add 0.2mL of Pseudomonas aeruginosa suspension, turn on a 150W xenon lamp to simulate sunlight (the visible light band is controlled at 420-630nm through optical elements), and carry out multiphase catalytic water disinfection reaction. Samples are collected every 20min, and the total disinfection reaction time is 80min.

[0123] In this case, 1.0wt% Cu / ZnIn2S4 is used to efficiently disinfect harmful bacteria, and the disinfecting effect on Pseudomonas aeruginosa is shown in Table 5. As can be seen from Table 5, after 80 minutes, Pseudomonas aeruginosa in the water was inactivated by 100%, which is consistent with the effect of Example 2.

[0124] S2: The 1.0wt% Cu / ZnIn2S4 in the residual liquid after 80 minutes of the disinfection reaction in step S1 is separated by centrifugation, and then washed alternately with ultrapure water and anhydrous ethanol for multiple times. After vacuum drying at 60°C, the sterilization experiment is carried out again to realize the recovery and regeneration of the catalyst of the disinfectant. The recovered catalyst is subjected to the next batch of sterilization experiments according to the method steps of step S1 to realize the recycling of the disinfectant. By analogy, the sterilization experimental data of the catalyst was recycled 5 times, and the experimental results are shown in Table 5. As shown in Table 5, after the 1.0wt% Cu / ZnIn2S4 of comparative example 5 was recycled 5 times, the sterilization effect decreased by 5%. This is because Cu ions have weak absorption in the infrared light region, which, to a certain extent, weakens the interaction between Cu ions and the carrier, making the loaded Cu ions easy to fall off after repeated use.

[0125] Comparative Example 6 Photothermal coupling subcritical technology (other visible light region) was used to prepare 1.0wt% Cu / ZnIn2S4 catalyst, and the steps were as follows:

[0126] 1) The preparation process of ZnIn2S4 is as described in Example 2.

[0127] 2) Disperse 2.1 mg CuCl2 and 100 mg ZnIn2S4 in 50 mL ultrapure water and disperse them evenly by ultrasonication; place the mixture into a photothermal coupling reactor made of stainless steel and seal the photothermal coupling reactor. Figure 1 The gas inlet on the photothermal coupling reactor is connected to the hydrogen cylinder through an inlet pipe with an inlet valve, the inlet valve and the outlet valve are opened, and hydrogen is passed to remove air and dissolved oxygen in the system. After that, the outlet valve and the inlet valve are closed, that is, no additional pressurized H2 is introduced into the photothermal coupling reactor to make the internal H2 reach a pressurized state, and the H2 pressure in the photothermal coupling reactor is 1 MPa at normal pressure; the temperature is raised to 160°C, the pressure is 2MPa, the xenon lamp light source is turned on, the xenon lamp power is 300W, the control band is 650-780nm, the reaction continues for 60min and then centrifuged, the obtained solid is washed with water and anhydrous ethanol 3 times respectively, and dried in vacuo at 60°C to obtain the 1.0wt% Cu / ZnIn2S4 catalyst with a three-dimensional structure.

[0128] The EDX image of the 1.0wt% Cu / ZnIn2S4 catalyst prepared in Comparative Example 6 is as follows: Fig.15 As shown, from Fig.15 It can be seen that in the 1.0wt% Cu / ZnIn2S4 catalyst of Comparative Example 6, the dispersion of Cu atoms on the surface of the ZnIn2S4 material is also highly dispersed compared with Example 2.

[0129] The 1.0wt% Cu / ZnIn2S4 catalyst prepared in Comparative Example 6 was used to disinfect harmful bacteria, and the operation steps were as follows:

[0130] S1: First, prepare a 10 8 CFU / mL of Pseudomonas aeruginosa suspension, then take 20mL PBS buffer solution and add 0.02g catalyst, ultrasonicate for 2min to ensure that the catalyst is evenly dispersed in the solution, then under magnetic stirring and room temperature of 25℃, add 0.2mL of Pseudomonas aeruginosa suspension, turn on a 150W xenon lamp to simulate sunlight (the visible light band is controlled at 420-630nm through optical elements), and carry out multiphase catalytic water disinfection reaction. Samples are collected every 20min, and the total disinfection reaction time is 80min.

[0131] In this case, 1.0wt% Cu / ZnIn2S4 is used to efficiently disinfect harmful bacteria, and the disinfecting effect on Pseudomonas aeruginosa is shown in Table 5. As can be seen from Table 5, after 80 minutes, Pseudomonas aeruginosa in the water was inactivated by 100%, which is consistent with the effect of Example 2.

[0132] S2: The 1.0wt% Cu / ZnIn2S4 in the residual liquid after 80 minutes of the disinfection reaction in step S1 is separated by centrifugation, and then washed alternately with ultrapure water and anhydrous ethanol for multiple times. After vacuum drying at 60°C, the sterilization experiment is carried out again to realize the recovery and regeneration of the disinfectant catalyst. The recovered catalyst is subjected to the next batch of sterilization experiments according to the method steps of step S1 to realize the recycling of the disinfectant. By analogy, the sterilization experimental data of the catalyst recycled 5 times are tested, and the experimental results are shown in Table 5. As shown in Table 5, the sterilization effect of 1.0wt% Cu / ZnIn2S4 in comparative example 6 decreased by 2% after being recycled 5 times. This is because the wavelength is close to the infrared light region, which has some slight effects on the anchoring effect of Cu ions, and the loaded Cu ions fall off in small amounts after repeated use. After the number of cycles reaches 20 times, the sterilization effect is significantly reduced compared with Example 2. Therefore, 420-630nm is the most suitable wavelength range for photothermal coupling technology.

[0133] Table 6 Comparison of sterilization effects of catalyst materials after 20 cycles

[0134] .

Claims

1. A method for preparing highly dispersed metal particle anchor catalyst based on photothermal coupling subcritical technology, characterized in that The following steps are involved: Step 1: Disperse the metal salt and the carrier material in ultrapure water, mix them evenly by ultrasonication, and then transfer them into a photothermal coupling reactor, wherein the photothermal coupling reactor is provided with a quartz window, and a light source is provided outside the quartz window; The metal salt is at least one of the nitrates and chlorides corresponding to copper, nickel and ruthenium; The carrier material is at least one of monometallic sulfide MoS2, polymetallic oxide CoFe2O4, and polymetallic sulfide ZnLn2S4; Step 2: introduce H2 or N2 into the mixed liquid in the photothermal coupling reactor to replace the air in the photothermal coupling reactor, then stop introducing the gas, seal the reactor and stir the mixed liquid, heat it to make the temperature in the reactor 150-220°C and the pressure 1.5-2.5MPa, turn on the light source to irradiate the mixed liquid, control the visible light band to 420-630nm, and keep the load under stirring for 30-90min; Step 3: After the mixed solution obtained in step 2 is cooled, it is centrifuged and the obtained solid is washed with ultrapure water and anhydrous ethanol and then vacuum dried to obtain a highly dispersed metal particle anchor catalyst.

2. A method for preparing a highly dispersed metal particle anchor catalyst based on light-thermal coupling subcritical technology as claimed in claim 1, characterized in that In step 1, the dispersion concentration of the carrier material in ultrapure water is 0.5-5 g / L, and the mass of the metal element in the metal salt is 0.5-4% of the mass of the carrier material.

3. A method for preparing a highly dispersed metal particle anchor catalyst based on light-thermal coupling subcritical technology as claimed in claim 1, characterized in that The light source in step 2 is a 200W-400W xenon lamp with a wavelength range of 420-630nm.

4. A method for preparing a highly dispersed metal particle anchor catalyst based on light-thermal coupling subcritical technology as claimed in claim 1, characterized in that In step 2, the temperature in the reactor is 160-200° C., the pressure is 1.5-2.0 MPa, and the stirring load time in step 2 is 60-80 min.

5. A highly dispersed metal particle anchor catalyst prepared by the method according to any one of claims 1 to 4, characterized in that The metal is copper, nickel or ruthenium, and the mass of the metal is 0.5-4% of the mass of the carrier material.

6. The use of the highly dispersed metal particle anchoring catalyst as claimed in claim 5 in photocatalytic disinfecting of harmful bacteria, characterized in that The metal is copper, the carrier material is monometallic sulfide MoS2 or polymetallic sulfide Znln2S4, the mass of the metal element is 1-4% of the mass of the carrier material, and the application of the highly dispersed metal particle anchored catalyst in photocatalytic harmful bacteria disinfection comprises the following process: adding the catalyst to a harmful bacteria solution, stirring at room temperature, and irradiating the solution with a 100-300W xenon lamp light source, controlling the visible light band at 420-630nm through optical elements, and carrying out a multiphase catalytic water disinfection reaction.

7. The use of the highly dispersed metal particle anchor catalyst as claimed in claim 5 in photocatalytic degradation of organic pollutants in water, characterized in that The metal is nickel, the carrier material is polymetallic sulfide Znln2S4, the mass of the metal element is 3-4% of the mass of the carrier material, and the highly dispersed metal particle anchor catalyst is used in the photocatalytic degradation of organic pollutants in water. The process is: adding the catalyst to the aqueous solution of organic pollutants, stirring, adjusting the pH value to 1±0.2, stirring at room temperature, first stirring for 20-60 minutes in a dark environment to reach adsorption-desorption equilibrium, and then performing a photocatalytic degradation reaction under irradiation with a 200-400W Xe lamp light source and a cutoff filter of 420 nm.

8. Use of the highly dispersed metal particle anchoring catalyst as claimed in claim 5 in a photocatalytic oxidation reaction.

9. The use according to claim 8, characterized in that The metal is ruthenium, the carrier material is multi-metal oxide CoFe2O4, the mass of the metal element is 3-4% of the mass of the carrier material, and the catalyst is used to catalyze the reaction of oxidizing HMF to prepare FDCA. The reaction process is: HMF, alkali, catalyst and oxidant are dispersed in water, after ultrasonic mixing, the mixed solution is transferred to a high-pressure reactor and sealed, and the temperature is raised to 100-130° C. and stirred for reaction for 8-12 hours; The mass of the catalyst is 70-80% of the mass of HMF, and the molar ratio of the alkali to HMF is 1.5-2:

1.

10. The use according to claim 9, characterized in that The oxidant is tert-butyl hydroperoxide, and the molar amount of the oxidant is 15-20 times the molar amount of HMF.

Citation Information

Patent Citations

  • Experiment device for evaluating performance of structured photothermal catalytic material and testing method

    CN109507362A

  • Preparation of monolithic catalyst and application method thereof

    CN110075854A